Designing Local Language Material based on Multilingual 4 in 1 in Merdeka Curriculum Implementation - Saidna Zulfiqar Bin Tahir; Susiati, Susiati; A Yusdianti Tenriawali; Geminastiti Sakkir (UNIB Press, 2023)
The death of 11 of the 71 local languages ​​in Maluku without a proper burial is a very sad thing for generations of speakers of these languages. Meanwhile, 71 other local languages ​​are threatened with extinction. Even though there has been a Maluku province regional regulation No. 14 of 2005 and Regional Regulation No. 3 of 2009 as well as central government policies through Minister of Education, Culture, Research, and Technology regulations No. 7 of 2022 concerning the independent curriculum. These efforts, up to now, have not produced effective results, so it is very urgent to research and revitalize it based on the needs and conditions of the Maluku people, especially on the island of Buru to prevent language death and extinction. Therefore, this research aims to develop 4 in 1 multilingual-based Maluku regional language teaching materials (Buru language) in implementing the Merdeka curriculum in Buru Regency. To achieve the objectives of this research, the appropriate research method to employ is Research and Development (R&D) with an analysis, design, development, implementation, and evaluation (ADDIE) model design. This design shows several research stages starting with analyzing the needs of students, teachers, and stakeholders as well as analyzing the situation in 6 Madrasah Tsanawiyah (MTs) schools in the Buru district. The results of data analysis will be used as material to design and develop syllabi, lesson plans, and Buru language textbooks in the 4 in 1 multilingual learning model, then develop textbook products and will be implemented in the independent curriculum and evaluated through experimental tests on small, medium and large scales